2007
DOI: 10.1099/mic.0.2007/007948-0
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic regulation of expression of two extracellular matrix-binding proteins and a haemolysin of Leptospira interrogans: differential effects on LigA and Sph2 extracellular release

Abstract: The life cycle of the pathogen Leptospira interrogans involves stages outside and inside the host. Entry of L. interrogans from moist environments into the host is likely to be accompanied by the induction of genes encoding virulence determinants and the concomitant repression of genes encoding products required for survival outside of the host. The expression of the adhesin LigA, the haemolysin Sph2 (Lk73.5) and the outer-membrane lipoprotein LipL36 of pathogenic Leptospira species have been reported to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
67
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 46 publications
6
67
0
1
Order By: Relevance
“…Physiological osmolarity serves as a cue for Leptospira to both initiate expression of genes (8) and release the LigB and Sph2 proteins into the extracellular space (37). Interestingly, previous studies have also demonstrated LigB-and Sph2-mediated binding of host homeostatic proteins (38,39), suggesting a role for these proteins in leptospiral attachment to host cells.…”
Section: Fig 2 the Lb139mentioning
confidence: 96%
“…Physiological osmolarity serves as a cue for Leptospira to both initiate expression of genes (8) and release the LigB and Sph2 proteins into the extracellular space (37). Interestingly, previous studies have also demonstrated LigB-and Sph2-mediated binding of host homeostatic proteins (38,39), suggesting a role for these proteins in leptospiral attachment to host cells.…”
Section: Fig 2 the Lb139mentioning
confidence: 96%
“…Using reasoning similar to that described above, WCPs and CSPs were subjected to immunoblot analysis using antiserum cross-reactive with L. interrogans Ig-like repeat domain protein 1 (LigA with a molecular mass of 128 kDa) (Fig. 1D) to assess the bacterial response to an osmotic shift (45,46). The LigA protein was detected in CSP samples, with pronounced reactivity being observed in CSP samples from L. interrogans exposed to 120 mM NaCl (Fig.…”
Section: Validation Of Methodology and Overview Of Wcps And Exoproteinsmentioning
confidence: 99%
“…ligB mRNA is upregulated in the bloodstream of infected rodent models, and Lig protein is detected in the kidneys of infected hamsters (24,25). L. interrogans and the closely related species L. kirschneri are typically cultivated under low-osmolarity conditions; exposure of the organisms to higher levels of osmolarity, such as those found in the host, causes the expression level of ligA and ligB to increase markedly (26,27).…”
mentioning
confidence: 99%